THE INFLUENCE OF GUIDED INQUIRY LEARNING MODELS TOWARDS STUDENT LEARNING OUTCOMES IN COST OF MATERIAL DYNAMIC FLUID IN CLASS XI SEMESTER I SENIOR HIGH SCHOOL 2 PERCUT SEI TUAN - Sari Marina Rumahorbo; Motlan Motlan; Elya Inoventa (UNIVERSITAS NEGERI MEDAN, 2019)
This research aims to determine the effect of guided inquiry learning model to student’s learning outcomes in the subject matter of momentum, impulse and collision in class X SMA N 1 Percut Sei Tuan. This research is a quasi experiment with group pre test-post test design. The population in the study was all students of class X MIA SMA N 2 Percut Sei Tuan. The research sample consisted of two classes with technique cluster random sampling that is, a class X MIA-3 as class experiment and X MIA-4 as the control class, each one amount to 30 students. The instrument used is achievement test in the form of 8 essay. Based on data analysis obtain that there is effect of guided inquiry learning model to student learning outcomes in the subject matter of momentum, impulse and collision in class X SMA N 2 Percut Sei Tuan. Keywords: guided inquiry, dynamic fluid, learning outcomes